Synthesis, crystal structure, optical, thermal, mechanical, dielectric and DFT studies of 3, 5-dimethylprazole:1, 3, 5-benzene tricarboxylic acid molecular adduct crystal. (April 2020) - Rajkumar, M.; Muthuraja, P.; Dhandapani, M.; Chandramohan, A.
Graphical abstract: Highlights: An organic adduct was synthesized and crystals grown in methanol-acetone solvent mixture. DMPBT crystal forms R 2 2 (8) and R 3 3 (11) ring motifs through OH…O, OH…N and NH…O hydrogen bonds. HOMO-LUMO band gap energy of the crystal was calculated to be 4.9076 eV using DFT. The crystal has very good thermal stability up to 220 °C. The first order hyperpolarizability(β) of DMPBT crystal was found to be 7.92073 × 10 −31 esu. Abstract: An organic molecular adduct, 3, 5-Dimethylpyrazole:1, 3, 5-benzene tricarboxylic acid was synthesized and single crystals grown in methanol-acetone (1:1) solvent mixture by slow solvent evaporation solution growth technique at room temperature. The formation of the molecular adduct and crystal structure have been confirmed by single crystal X-ray diffraction studies and NMR spectroscopic techniques. Further, the title crystal belongs to monoclinic crystal system with space group, P21 /c and the supramolecular architecture of adduct involves extensive intermolecular O-H…N, N-H…O, O-H…O and C-H…O hydrogen bonding interactions. UV–Vis-NIR spectrum was recorded to find out the lower cut-off wavelength, percentage transmission and optical band gap energy. The fluorescence properties of the title crystal were identified by Photoluminescence spectral studies. Fourier transform infrared (FT-IR) spectral analysis was carried out to confirm the presence of various functional groups in the grown crystal. The quantum chemical analyses were performed by density functional theory (DFT) using B3LYP/6-311G (d, p) basis set. The thermal and mechanical properties of the grown crystal have been investigated by TG/DTA analyses and Vickers micro hardness measurement, respectively. The dielectric behaviours of title single crystal have also been investigated as a function of frequency at different temperatures.